2021
DOI: 10.3390/jof7010059
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 1,3 β-d-Glucan Assay for Guidance in Antifungal Stewardship Programs for Oncologic Patients and Solid Organ Transplant Recipients

Abstract: The implementation of 1,3 β-d-glucan (BDG) has been proposed as a diagnostic tool in antifungal stewardship programs (ASPs). We aimed to analyze the influence of serum BDG in an ASP for oncologic patients and solid organ transplant (SOT) recipients. We conducted a pre–post study. In the initial period (PRE), the ASP was based on bedside advice, and this was complemented with BDG in the post-period (POST). Performance parameters of the BDG assay were determined. Antifungal (AF) use adequacy was evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Of these, 7 studies demonstrated a reduction ranging from 11.6% to 59.0% [ 20 , 21 , 25 , 27 , 29 , 30 , 33 ]. Decrease in antifungal cost was reported by 10 studies [ 20 , 21 , 23 , 25 , 26 , 28 , 30 , 31 , 33 , 35 ], of which 5 studies demonstrated a cost-savings ranging from 13.5% to 50.6% ( Table 2 ) [ 26 , 30 , 31 , 33 , 35 ]. Alfandari et al reported a cost-savings of €2 million within 7 years (2005–2012) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 7 studies demonstrated a reduction ranging from 11.6% to 59.0% [ 20 , 21 , 25 , 27 , 29 , 30 , 33 ]. Decrease in antifungal cost was reported by 10 studies [ 20 , 21 , 23 , 25 , 26 , 28 , 30 , 31 , 33 , 35 ], of which 5 studies demonstrated a cost-savings ranging from 13.5% to 50.6% ( Table 2 ) [ 26 , 30 , 31 , 33 , 35 ]. Alfandari et al reported a cost-savings of €2 million within 7 years (2005–2012) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Heil et al demonstrated a cost-saving of US$415 per patient based on switching from a more expensive echinocandin therapy to fluconazole therapy and reduced mean time to targeted therapy in the postimplementation group [ 23 ]. Likewise, Machado et al reported less use of caspofungin (21.2% vs 6.2%; P = .002) and higher use of fluconazole (18.8% vs 45.5%; P < .001) in the postintervention group with AFS, complemented with BDG, which aimed to evaluate antifungal adequacy and management in hospitalized patients with solid tumor or solid organ transplantation and receiving systemic AFT [ 26 ]. Both studies highlighted the importance and benefit of early de-escalation to lower-spectrum antifungals.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have convincingly shown that antifungal stewardship reduces mortality in the hospitalised patient. [47][48][49][50][51][52] The basic elements of successful stewardship are: (1) comprehensive knowledge and continuous reference to the best clinical guidance on fungal disease management; (2) a primary focus on the best quality care, not on cost saving, as some expensive antifungals are the best choice (stopping unnecessary therapy is what saves money); (3) clinical experience to know when to infer likely results if not yet available or samples cannot or were not taken. One important tool to assist in top quality fungal disease stewardship is rapid diagnostic services, notably mycology results, but also imaging.…”
Section: Antifungal Stewardshipmentioning
confidence: 99%
“…Many AFS programmes designed in tertiary centres have succeeded in reducing mortality 32 34 improving the appropriateness of antifungal use and decreasing the economic burden of new antifungals 35 , 36 with the additional support of fungal biomarkers. 37 , 38 AMS has been shown to reduce the use of antifungals by increasing prescribers’ awareness and mitigating risk factors for fungal infections. 39 , 40 …”
Section: General Stewardship Principlesmentioning
confidence: 99%